Pulmonary artery diameter to predict pulmonary hypertension in pulmonary sarcoidosis. Issue 2 (22nd October 2015) - Huitema, Marloes P.; Spee, Marcela; Vorselaars, Veronique M.M.; Boerman, Sanne; Snijder, Repke J.; van Es, Hendrik W.; Reesink, Herre J.; Grutters, Jan C.; Post, Marco C.
Pulmonary hypertension (PH) is a known complication of pulmonary sarcoidosis with a prevalence ranging from 5% to 74% [1]. The aetiology of PH in sarcoidosis is not fully understood. Usually, it is attributed to the destruction of the distal capillary bed by lung fibrosis and/or chronic hypoxaemia. However, the severity of PH does not correlate consistently with the degree of pulmonary fibrosis, and PH exists in sarcoidosis patients without fibrosis, suggesting a multifactorial mechanism. The presence of PH is associated with a poor prognosis, and early diagnosis and treatment might improve outcome [1]. Echocardiography should always be performed when PH is suspected [2]. However, the accuracy of echocardiography in patients with interstitial lung diseases is often limited due to poor image quality and unreliable tricuspid regurgitation signal to measure the right ventricular systolic pressure (RVSP) [3]. Further invasive investigation with the gold standard, right heart catheterisation (RHC), is often required. In order to optimise the noninvasive diagnostic approach, there is a need for more accurate predictors of PH. Computed tomography (CT) may raise suspicion of PH in symptomatic patients or those examined for unrelated indications by showing an increased pulmonary artery (PA) diameter (≥29 mm) and PA diameter/ascending aorta diameter (AAD) ratio (≥1.0) [2]. Similarly, PA diameter indexed to body surface area (BSA) has been suggested as possible predictor of PH. However, these parameters have never been investigated in pulmonary sarcoidosis specifically. Pulmonary artery indexed for body surface area is the most accurate predictor for PH on CT in pulmonary sarcoidosis http://ow.ly/T863m